Can Aquatic Invertebrates within Public Aquaria Fit the Five Domain Welfare Model? - Perkins, Kerry (Journal of applied animal ethics research, 2021)
Abstract Welfare within zoos and aquariums has come under increasing scrutiny due to the change in public opinion of animals in captivity. It is vital that as an industry mechanisms and frameworks are in place to determine welfare of animals within our care. Due to potential bias in current welfare models toward terrestrial vertebrates, it is important to determine whether they can be utilised in differing environments such as aquariums. Using the most recent five domain model (Mellor, 2017) the possible application within public aquaria is discussed, considering each domain in respect to aquatic invertebrates, an often-neglected group of organisms when considering welfare in aquaria. This review highlights the additional considerations needed when applying the five domain model to this diverse group of organisms. Furthermore, the identification of gaps within the current literature is discussed in respect to whether the full five domain model can be currently be applied at this time.